2019
DOI: 10.3389/fmed.2019.00115
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Skin: Lessons From Transcriptomic Studies

Abstract: In 2016, a special interest group from the International Forum for the Study of Itch defined sensitive skin (SS) as a syndrome that manifests with the occurrence of unpleasant sensations (stinging, burning, pain, pruritus, and tingling sensations) after stimuli that should not cause a reaction, such as water, cold, heat, or other physical and/or chemical factors. The pathophysiology of sensitive skin is still poorly understood, but the symptoms described suggest inflammation and peripheral innervation. Only tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Some genetic studies have shown that a wide range of genes may be involved in the pathogenesis and suggested potentially associated pathways. 29 Nonetheless, the effect of exposome is probably very high. As shown in the present study, sensitive skin is not only related to contact-based environmental factors but also to systemic exposome factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some genetic studies have shown that a wide range of genes may be involved in the pathogenesis and suggested potentially associated pathways. 29 Nonetheless, the effect of exposome is probably very high. As shown in the present study, sensitive skin is not only related to contact-based environmental factors but also to systemic exposome factors.…”
Section: Discussionmentioning
confidence: 99%
“…Because subjects with sensitive skin had a two‐fold increase in the familial history of sensitive skin, genetic factors may play a role. Some genetic studies have shown that a wide range of genes may be involved in the pathogenesis and suggested potentially associated pathways 29 . Nonetheless, the effect of exposome is probably very high.…”
Section: Discussionmentioning
confidence: 99%
“…Two transcriptomic studies have been performed to compare skin samples of patients with sensitive skin and controls using DNA microarray [55] or RNA sequencing [56]. Although the small sample size could make the results debatable, the authors showed the involvement of innervation and Merkel cells in the pathophysiology of sensitive skin [57]. They also suggested keratinocytic involvement and a putative role of innate immunity [57] or adiponectin deficiency in sensitive skin [55].…”
Section: Arguments For Neuro-keratinocytic Interactionsmentioning
confidence: 99%
“…Although the small sample size could make the results debatable, the authors showed the involvement of innervation and Merkel cells in the pathophysiology of sensitive skin [57]. They also suggested keratinocytic involvement and a putative role of innate immunity [57] or adiponectin deficiency in sensitive skin [55].…”
Section: Arguments For Neuro-keratinocytic Interactionsmentioning
confidence: 99%
“…Phototype I-IV [21] Fair skin, susceptible to sunburn [5,16] Susceptibility to blushing and/or flushing [5,16] Skin pigmentation [5,48] Dry skin [16,21,46,47] Ethnicity a [14] Gender [5,9,16,21,49] Menstrual cycle [5,18,50] Age [5,51,52] Incontinence [53] Familial and genetic links [21,[54][55][56] a The perception of sensitive genital skin is significantly higher among African-Americans compared to Caucasians.…”
Section: Skin Typementioning
confidence: 99%